2019
DOI: 10.1186/s12882-019-1271-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes on sarcopenia and mortality in patients undergoing hemodialysis

Abstract: Background Sarcopenia has become a serious disorder in modern society. Chronic kidney disease requiring dialysis and diabetes are some of the disorders that accelerate the onset and progression of sarcopenia. We, therefore, investigated the prevalence of sarcopenia in patients undergoing hemodialysis (HD) and confirmed the impact of diabetes mellitus (DM) on this population. Methods This study included 308 patients whose muscle strength and mass had been evaluated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
116
3
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(136 citation statements)
references
References 24 publications
13
116
3
4
Order By: Relevance
“…These findings suggest that uremia may have a role in the pathogenesis AF, but the mechanism remains to be investigated. While a previous 9-year cohort study in Japan showed that DM was highly associated with all-cause mortality in patients undergoing hemodialysis (adjusted HR: 2.39; p < 0.001) [26], the present study showed that DM was not significantly associated with the risk of mortality. This discrepancy may result from the difference in race, glucose control status or relative short study period of the present study.…”
Section: Discussioncontrasting
confidence: 97%
“…These findings suggest that uremia may have a role in the pathogenesis AF, but the mechanism remains to be investigated. While a previous 9-year cohort study in Japan showed that DM was highly associated with all-cause mortality in patients undergoing hemodialysis (adjusted HR: 2.39; p < 0.001) [26], the present study showed that DM was not significantly associated with the risk of mortality. This discrepancy may result from the difference in race, glucose control status or relative short study period of the present study.…”
Section: Discussioncontrasting
confidence: 97%
“…The inverse relationship between Kt/V and physical performance was consistently shown in other studies, suggesting that this relationship is likely to be a universal phenomenon [24,34,36,46]. We speculate that the low muscle mass and subsequent decreased volume of distribution of urea in the body (V) in patients with low GS and HS resulted in a relative increase in the value of Kt/V without affecting the true dialysis efficacy [47].…”
Section: Discussionsupporting
confidence: 61%
“…Compared to the elderly population, in which the prevalence of sarcopenia is 11% [33], CKD patients are likely to be much more prone to its occurrence, with an estimated prevalence of 30 -60% [20,21,24,[34][35][36]. The two main components of sarcopenia, muscle strength and mass, are dissociated in the setting of ESRD, and the muscle strength is more important than muscle mass in terms of patient outcomes [20,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the elderly population, in which the prevalence of sarcopenia is 11% [32], CKD patients are likely to be much more prone to its occurrence, with an estimated prevalence of 30 -60% [20,21,24,[33][34][35]. The two main components of sarcopenia, muscle strength and mass, are dissociated in the setting of ESRD, and the muscle strength is more important than muscle mass in terms of patient outcomes [20,34].…”
Section: Discussionmentioning
confidence: 99%